Pengaruh Technical Criteria, Economic Criteria dan Legalistic Criteria terhadap Perilaku Brand Switching Konsumen pada Pembelian Sepeda Motor Honda Vario di Pekalongan Lampung Timur - Sandi, Canu Pratama; Rahayu, Sri Retnaning (Jurnal Manajemen DIVERSIFIKASI, 2021)
To survive in the competition for means of transportation, Honda companies always strive to provide the best quality and service to consumers, by providing products that are of good quality, always innovative, in accordance with the times, at affordable prices in order to build a deep emotional relationship between Honda products and consumer. It is important for Honda companies to understand between emotional branding and brand switching so that the company can create a product that suits consumer needs, especially motorbikes and can provide a high emotional feeling between consumers and products so that they do not brand switching to other brands. The purpose of this study was to find out if Technical Criteria, Economic Criteria and Legalistic Criteria effect simultanneously on Consumer Brand Switching Behavior in Purchasing a Honda Vario Motorcycle. In this study using primary data and secondary data, the research method used is judgment sampling which is one type of purposive sampling, where the researcher chooses a sample based on certain characteristics, namely Honda Vario motorcycle consumers in Pekalongan, East Lampung, with a total sample of 60 people. The data analysis technique used is validity test, reliability test, normality test, linearity test and homogeneity test. Testing the analysis model in this study using multiple linear regression analysis, T test, F test and R determination. Based on the results of research using the T test, it is found that the technical criteria do not have a significant effect on consumer brand switching for Honda Vario motorcycle purchases, Economic criteria have a positive and significant effect on consumer brand switching for Honda Vario motorcycle purchases and Legalistic criteria have a positive and significant effect on brand switching consumers on the purchase of a Honda Vario motorcycle. From the F test, technical criteria, economic criteria and legalistic criteria together have a positive and significant effect on consumer brand switching for purchasing a Honda Vario motorcycle.